Exposure to Doxorubicin Modulates the Cardiac Response to Isoproterenol in Male and Female Mice - Kevin Agostinucci; Marianne K. O. Grant; Wongel Melaku; Chandini Nair; Beshay N. Zordoky (MDPI AG, 2023)
Sex is a salient risk factor in the development of doxorubicin-induced cardiotoxicity. Sex differences in the heart's ability to respond to hypertrophic stimuli in doxorubicin-exposed animals have not been reported. We identified the sexual dimorphic effects of isoproterenol in mice pre-exposed to doxorubicin. Male and female intact or gonadectomized C57BL/6N mice underwent five weekly intraperitoneal injections of 4 mg/kg doxorubicin followed by a five-week recovery period. Fourteen days of subcutaneous isoproterenol injections (10 mg/kg/day) were administered after the recovery period. Echocardiography was used to assess heart function one and five weeks after the last doxorubicin injection and on the fourteenth day of isoproterenol treatment. Thereafter, mice were euthanized, and the hearts were weighed and processed for histopathology and gene expression analysis. Doxorubicin did not produce overt cardiac dysfunction in male or female mice before starting isoproterenol treatment. The chronotropic response to a single isoproterenol injection was blunted by doxorubicin, but the inotropic response was maintained in both males and females. Pre-exposure to doxorubicin caused cardiac atrophy in both control and isoproterenol-treated male mice but not in female mice. Counterintuitively, pre-exposure to doxorubicin abrogated isoproterenol-induced cardiac fibrosis. However, there were no sex differences in the expression of markers of pathological hypertrophy, fibrosis, or inflammation. Gonadectomy did not reverse the sexually dimorphic effects of doxorubicin. Additionally, pre-exposure to doxorubicin abrogated the hypertrophic response to isoproterenol in castrated male mice but not in ovariectomized female mice. Therefore, pre-exposure to doxorubicin caused male-specific cardiac atrophy that persisted after isoproterenol treatment, which could not be prevented by gonadectomy.